A arte no tempo da sua dispersão concentrada - Miguel Leal (2007)
Art at the time of its concentrated dispersion Dispersion and concentration emerge as inevitabilities pursuing contemporariness. Every day we are asked, from politics to economy, from companies to the university, an effort to concentrate and focus. Such an atomization is the result of a combination between a certain dispersion and a certain concentration. Two movements into a single one. The best example of this circularity is the phenomenon we refer to as globalization. Its policy is based on segmentation, according to a logic that is still modern at its core. Global and undifferentiation producing wholeness needs both dispersion and segmentation as enclosing, dividing and systematizing instruments. Increasing art standardization and culture industrialization may be the main signs of globalization in the field of aesthetics. With art standardization, we see the idea of an art form in its singularity is stretched to the limit; but also its identitary multiplication, its subject division. With culture industrialization, we witness art disappearing and melting into the vague magma of entertainment. The answer involves searching for dispersion as a means to accomplish the cross contaminations art is made of, and refusing it as a guarantee of a place for art.